Changes in the distribution and number of St. Anthony Evening Primrose between 1994 and 2024 - Housley, Austin J.; Baird, Gary I.; Burchfield, David R.; Petersen, Steven L.; Whiting, Jericho C. (Frontiers in Conservation Science, 2025)
IntroductionRare and endemic plants that inhabit sand dunes are of conservation concern across the world. The St. Anthony Evening Primrose (Oenothera psammophila, (A. Nelson & J.F. Macbr.) W.L. Wagner, Stockhouse & Klein) is a rare endemic plant that occurs on the St. Anthony Sand Dunes (SASD) in Idaho, USA. This evening primrose is classified by the Bureau of Land Management (BLM) as a range-wide imperiled species with high endangerment risk and was listed as a candidate species under the Endangered Species Act in 1975, but was removed from candidacy in 1996 after extensive population estimates. Little research has been conducted on this species since these population estimates conducted by the BLM in 1994.MethodsWe conducted surveys in 2024 to compare the current geographic distribution and number of individuals of this species with similar data collected in 1994. We hypothesized that the distribution and number of these plants have decreased in the last 30 years.ResultsIn 1994, it was documented that the St. Anthony Evening Primrose occupied 1,403 ha with 38,426 plants. In 2024, we documented that the St. Anthony Evening Primrose covered 829 ha (41% decrease; X2 = 106.85, p < 0.0001) with 19,737 plants (49% decrease; X2 = 3035.9, p < 0.0001). The distribution and number of plants decreased in two of the three regions in our study area but did not decrease in one of those regions. From 1994 to 2018–2021, there has been a 16,909% increase in the number of Off-Highway Vehicles (OHV) on the SASD during June, which is likely correlated to the decrease in distribution and number of St. Anthony Evening Primrose.DiscussionAlthough we documented decreases in population distribution and number of plants in two regions of our study area, our data precluded us from quantifying the extent of those decreases that were caused by natural dune movement, variation in precipitation and soil moisture, or OHV use. Our results, however, do provide biologists with information about this species that can be used for land-use management plans and comparisons with future studies of the St. Anthony Evening Primrose. Lastly, our results support reevaluating the S-rank for this species.